Implementasi dan Pengungkapan Good Corporate Governance pada Bank Umum Syariah Milik BUMN - Masiyah Kholmi (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to analyze the implementation and disclosure level of good corporate governance of the state-owned Commercial Bank Sharia in Indonesia 2017-2020 Methodology/Approach:  This research uses a content analysis method. The data was collected using documentation techniques in the form of annual the state-owned Commercial Bank Sharia reports on the websits of each bank. Findings: The research results show that the state-owned commercial bank sharia has implemented and expressed good corporate governance. BNI Sharia and BRI Sharia are included in the "good" predicate and Bank Sharia Mandiri is included in the "very good" predicate. Bank Sharia Mandiri has the highest governance disclosure score, namely 100%, then BRI Sharia 85% and BNI Sharia 83%. BRI Sharia and BNI Sharia are expected to have a higher score/rating for disclosure of good corporate governance in the future. Practical and Theoretical Contribution/Originality:  This research can be essential information for stockholder and stakeholders in the implementation and good corporate corporate  and haria banks governance disclosure . Research Limitation: The research object only uses the state-owned Commercial Bank Sharia registered with the OJK in 2017 to 2020 or before the merger of Bank Sharia Indonesia (BSI).